(untitled) (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out in the field laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh, to investigate the flowering pattern, floral and pod abscission under untreated and GABA (mixture of GA3 and Abscissic acid) treated soybean and their trends concern to yield. The variety of soybean PB-1 (Shohag) was used in the investigation. GABA at 0.5, 1.0 and 2.0 mg L-1 of water with a control (only water) were used for foliar spray. Flower and pod initiation started from 54 and 60 DAS in all plants irrespective to GABA treatment. Flower production trend showed a deltoid pattern where pod production was gradually increased and slowed down at 74 DAS but not in GABA treated plant. The 4th node produced the highest number of flowers, then decreased and got zigzag pattern in upper nodes. GABA treated plants produced more nodes per plant and followed lower trend in flower and pod abscission indicated the efficacy of higher yield. Keywords: Flowering pattern; Floral abscission; Yield; Soybean; GABA DOI: 10.3329/jbau.v8i1.6394 J. Bangladesh Agril. Univ. 8(1): 29-33, 2010